Perlindungan Hukum Terhadap Hak Untuk Membela diri bagi Anggota Polri yang di sidang Kode Etik dengan Vonis Pemberhentian Tidak Dengan Hormat - Prasetia, Andy; Yuningsih, Henny; Albariansyah, Hamonangan (Dinasti Research, 2025)
Legal Protection of the Right to Self-Defense for Members of the Indonesian National Police Tried in Code of Ethics Hearings with a Dishonorable Discharge Verdict,” examines the tension between Polri’s disciplinary mechanisms and Indonesia’s criminal justice system. In practice, police personnel accused of criminal offenses are frequently subjected to Dishonorable Discharge (PTDH) through code of ethics hearings before a final criminal judgment (inkracht van gewijsde) is issued. This raises questions about the protection of the right to self-defense, the presumption of innocence, and the principle of justice. The study aims to (1) analyze how legal protection for self-defense should be guaranteed in Polri’s code of ethics hearings, and (2) assess whether PTDH imposed prior to a binding criminal verdict is consistent with the principles of Indonesian law. Findings indicate that, while regulations mandate adherence to audi et alteram partem, the presumption of innocence, and procedural safeguards under the Penal Code and Code of Criminal Procedure, in practice PTDH is often applied prematurely, undermining legal certainty and fairness. Case comparisons, including Brigadier Andriansyah (pre-inkracht) and Bripka Yuswindra (post-inkracht), highlight inconsistent practices within the institution. The research concludes that PTDH should only be executed after a final criminal judgment, thereby ensuring substantive justice, legal certainty, and the protection of fundamental rights. Recommendations include harmonizing disciplinary and criminal justice processes and revising internal Polri regulations to align with constitutional and criminal law principles.